2017
DOI: 10.1039/c7cp00092h
|View full text |Cite|
|
Sign up to set email alerts
|

The aromaticity of dicupra[10]annulenes

Abstract: An extensive theoretical investigation of the electronic structure of a tested fair model dicupra[10]annulene compound, based on the analysis of atom-pair delocalization indices, Bader's molecular graph, the inspection of the canonical molecular orbitals, the z components of their Nuclear Independent Chemical Shifts, NICS(0), and the normalized Giambiagi multicenter delocalization indices, concludes that the perimeter aromaticity of the dicupra[10]annulene ring is consistent with both 10 and 14 π-electron Hück… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
1
36
1
Order By: Relevance
“…
Magnetic aromaticity and antiaromaticityo f closed shell metalloaromaticsw ith 4d transition metals (Nb, Tc ,R h) is strictly correlatedw ith the orbital topology (Mçbiuso rH ückel) of their p-HOMO, investigated computationally with DFT methods. As urprisingly simple rule emerged:t he metallacycle is aromatic (antiaromatic) when the number of p MOs is even and the p-HOMOi so f Mçbius( H ückel) topology-and vice versa when the numbero fp MOs is odd.Recent reports aboutM çbiusa romatic osmapentalenes [1] and Hückel aromatic dicupra[10]annulene tetraanions [2] spikedarenewed interest in understanding the aromaticity of conjugated metallacycles; [3] ap resumably familiar concept, since R. Hoffmann's insightful proposal and the subsequent preparation of the first osma- [4] or iridabenzenes. [5] However,o ne of the most puzzlingf acts about metallabenzenes is that they seem to be limited to late or middle transition metal elements, whereas early transition metals do not seem to form metallabenzenes at all, and coinage metals appear to avoid being involved in neutral( rather than anionic) aromatics.
…”
mentioning
confidence: 99%
“…
Magnetic aromaticity and antiaromaticityo f closed shell metalloaromaticsw ith 4d transition metals (Nb, Tc ,R h) is strictly correlatedw ith the orbital topology (Mçbiuso rH ückel) of their p-HOMO, investigated computationally with DFT methods. As urprisingly simple rule emerged:t he metallacycle is aromatic (antiaromatic) when the number of p MOs is even and the p-HOMOi so f Mçbius( H ückel) topology-and vice versa when the numbero fp MOs is odd.Recent reports aboutM çbiusa romatic osmapentalenes [1] and Hückel aromatic dicupra[10]annulene tetraanions [2] spikedarenewed interest in understanding the aromaticity of conjugated metallacycles; [3] ap resumably familiar concept, since R. Hoffmann's insightful proposal and the subsequent preparation of the first osma- [4] or iridabenzenes. [5] However,o ne of the most puzzlingf acts about metallabenzenes is that they seem to be limited to late or middle transition metal elements, whereas early transition metals do not seem to form metallabenzenes at all, and coinage metals appear to avoid being involved in neutral( rather than anionic) aromatics.
…”
mentioning
confidence: 99%
“…In order to understand the contribution from different resonance structures as obtained from the NBO results, the CMO‐NICS calculations are performed . For borylene, the contribution to the NICS(0) value from different CMO and NBO are represented in Figures and , and all others are shown in Figures S1‐S22.…”
Section: Resultsmentioning
confidence: 99%
“…Grande-Aztatzi et al claimed that the annulene structures without substituents exhibit little deviation from the geometry in the substituted molecules. 18 However, this does not hold for A 4 and B 4 . The planar unsubstituted A 4 structure does not represent the experimental B 4 structure very well, since the rings in B 4 are twisted as shown in Figure 14.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggested that structure A 4 is even more aromatic than naphthalene. 18 Molecular-orbital analysis of the aromatic properties of A 2 and A 4 has recently been reported by An et al 27 They also calculated nucleus independent chemical shifts (NICS(0) zz ) and anisotropy of the induced-current densities (ACID) functions. 17,28 The NICS(0) zz and ACID calculations suggested that A 4 is aromatic and A 2 is antiaromatic.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation